The Influence of Halal Awareness and Food Quality Standards on Purchasing Intentions at Mujigae Restaurant - Mutmainah Arsyad; Nurvie Fuady; Ahmad Nuh; Naning Zuliarti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study explores the influence of halal awareness and food quality standards on purchasing intentions at Mujigae Restaurant. As the demand for halal food rises, understanding how these factors affect consumer behavior is crucial for businesses in the food industry. Utilizing a quantitative approach, data were collected through surveys distributed to 200 customers. The analysis revealed that both halal awareness and perceptions of food quality significantly impact purchasing intentions. Specifically, higher levels of halal awareness correlate with increased customer satisfaction and loyalty, while superior food quality enhances the overall dining experience. These findings suggest that enhancing halal awareness and maintaining high food quality can lead to increased customer retention and brand loyalty. This research provides valuable insights for restaurant management in developing effective marketing strategies to attract and retain customers in a competitive market. Ultimately, understanding these dynamics is essential for restaurateurs aiming to build lasting relationships with consumers while ensuring compliance with dietary laws. The results underscore the importance of integrating halal practices and high-quality standards to meet consumer expectations effectively.